NON-PERFORMING LOANS AND BANKS’ PROFITABILITY:EVIDENCE FROM NORTH MACEDONIA - Spaseska, Tatjana; Odzaklieska, Dragica; Risteska-Jankuloska, Aneta (Horizons - International Scientific Journal, 2022)
One of the basic preconditions of establishing dynamic economic development is founding a stable and contemporary banking system. Namely, the commercial banks are the backbones of the financial system of each country, especially in developing countries such as North Macedonia where the capital market is in initial phase of development. Consequently the banks’ loans are the main source for financing the businesses which in turn contributes to the economic development of the countries. Loans play dominant role in banks’ activities and they are related with credit risk. Therefore, the banks usually want it to be a performing one, since its nonpayment leads to incidence of huge loss. Consequently, the quality of credit portfolio determines the performance of the banks and it is a crucial factor affecting the profitability of individual banks and the entire banking sector. In the relevant literature, one of the most commonly used proxies of banks’ credit portfolio quality is non-performing loans ratio (NPLs).Regarding this, the main objective of the paper is to investigate the relationship between the non-performing loans and banks’ profitability in the Macedonian Banking System.